Vent’anni di elezione diretta del sindaco a Bologna - Marta Regalia; Marco Valbruzzi (QOE-IJES, 2016)
The article retraces the last 20 years of direct mayoral election in Bologna. It shows how the changes in institutional and electoral settings influenced both the party system and voters' electoral responses. By analysing the electoral history of the city, we also show that personalization raised, electoral competition became more (bi)polarized, electoral turnout gradually decreased, voting results became less and less predictable attenuating Bologna past exceptionalism. This article fills a gap in a literature that has not yet offered a longitudinal study of electoral changes in Bologna since the 1990s. More precisely, the article gives an analysis of both the political supply and the electoral flows to understand how party system has changed and if and how voters have become more mobile.